Airway morphology, hyoid position, and serum inflammatory markers of obstructive sleep apnea in children treated with modified twin-block appliances - Jun Duan; Wanyuan Xia; Xuelei Li; Feng Zhang; Fan Wang; Mengwei Chen; Qian Chen; Bing Wang; Bing Li (BMC Oral Health)
Abstract Objective To investigate the effects of modified twin-block appliances (MTBA) on obstructive sleep apnea (OSA) and mandibular retrognathia and the changes in the upper airway, hyoid bone position, and hypoxia-related inflammatory marker levels in children with OSA. Methods This study included children with OSA and mandibular retrognathia and those with class I without mandibular retrognathia (n = 35 each). The experimental group comprised children with OSA and mandibular retrognathia managed using MTBA. Postoperative and preoperative polysomnography, lateral cephalometric radiographs, and peripheral blood samples were collected. The control group comprised children with class I without mandibular retrognathia. Results Following MTBA management, the experimental group exhibited decreased apnea–hypopnea index and increased lowest arterial oxygen saturation level (P < 0.05). Sella- and subspinale-nasion-supramental angles significantly increased and decreased, respectively (P < 0.05). Posterior soft palatal–posterior pharyngeal wall distance, apical palatal–middle pharyngeal wall distance, posterior airway space, epiglottis valley–hypopharyngeal wall distance, hyoid–prevertebral plane distance, and distance from the superior anterior point of the hyoid bone to the inferior anterior point of the third cervical spine significantly increased, whereas distance from the superior anterior point of the hyoid bone to the mandibular plane decreased (P < 0.05). Conclusions Children with OSA (n = 35) were managed using MTBA, which relieved the mandibular retrognathia deformity, widened the upper airway space, moved the hyoid bone forward and upward, and improved the sleep monitoring indicators. Thus, MTBA can achieve satisfactory therapeutic effect in children with OSA and mandibular retrognathia with mandibular advancement.